Mercenary networks in Greek historiography - Sebastiani, Breno Battistin (Romanitas - Revista de Estudos Grecolatinos, 2026)
This text examines key steps from ancient Greek historians in which the actions of mercenaries are narrated from the perspective of the support networks they constituted. The aim is to highlight other elements that made the relationship between mercenaries, regimenters and communities of either origin or reception something more complex than just a relationship of payment for services performed. Finally, two consequences of the coordinated action of these mercenaries are discussed: on the one hand, their transformation into a reserve support base; on the other, and perhaps the most significant consequence, the danger that the presence of these mercenaries in a community entailed as something not always just latent, especially when they were motivated to act in a concerted manner and had opportunities to do so.
Keywords: Networks; Mercenaries; Migrants; Greek historiography